Understanding the needs of postpartum emerging adults with substance use disorders to improve recovery supports - Cioffi, Camille C.; Lewis, Lauren E.; Gau, Jeff (Frontiers in Public Health, 2025)
IntroductionPostpartum is a critical time point to support recovery among emerging adults with substance use disorders (SUD), however, support for postpartum emerging adults with SUD is insufficient. The goal of the current study was to identify key intervention objectives to improve recovery services for postpartum emerging adults with SUD.MethodsWe conducted a needs assessment with 100 women with past or present SUD. We asked women to report on their postpartum experiences retrospectively for post-pregnancy experiences between the ages of 18–29. Participants provided information on their pregnancy experiences and challenges. They also provided responses to open-ended questions to inform solutions to address challenges.ResultsThe top challenges for postpartum emerging adults included anxiety and depressive symptoms, economic resources, and lack of intimate and supportive social relationships. Participants described solutions to destigmatize societal perceptions of postpartum emerging adults with SUD, provide mental health services that are responsive to social challenges, provide practical economic assistance, improve awareness of services, and support the formation of informal support networks.DiscussionThis study provides insights on the needs of postpartum emerging adults. These data are actionable for both researchers and practitioners to inform recovery services improvements.